ADAPTASI BUDAYA JAWA DAN ACEH MELALUI UNSUR BAHASA DALAM MENINGKATKAN INTERAKSI SOSIAL (STUDI DI GAMPONG JANTHO BARU KECAMATAN KOTA JANTHO KABUPATEN ACEH BESAR) - Fatimah, Adihatul Fatimah (JOISCOM (Journal of Islamic Communication), 2025)
Cultural diversity creates social beauty in a region or country. However, cultural differences also present obstacles in adapting to other cultures. Cultural adaptation is important for someone in social interactions, especially those in multicultural areas such as Indonesia. Gampong Jantho Baru, Kota Jantho District, Aceh Besar Regency, the majority of the population are immigrants from Java Island who have a different culture from Aceh. The multicultural society in this village is influenced by the transmigration program that began in 1986. Over time, the Javanese people began to adapt to Acehnese culture. However, language differences become an obstacle in the adaptation efforts so that there are Javanese people who cannot speak Acehnese even though they have lived there for a long time. The purpose of this study is to analyze how cultural adaptation through language elements improves social interaction between Javanese and Acehnese people in Gampong Jantho Baru. This study also identifies factors that influence the inability of Javanese people to master the Acehnese language. This study uses qualitative methods. The data collection techniques are through observation, interviews and documentation. The results of the study show that, although there are difficulties in learning the Acehnese language, social interaction is still well established through the use of Indonesian as a Lingua Franca. The environment with the dominance of Javanese society is the main obstacle for immigrants in mastering the Acehnese language. However, the open and tolerant attitude of the Acehnese people helps to realize harmonious social relations. The conclusion of this study is that cultural adaptation through language elements in improving social interaction does not only depend on mastery of the local language. But also the use of Indonesian and the tolerant attitude of the local community in maintaining diversity and social harmony. Keywords: Cultural Adaptation, Language, Social Interaction, Java-Aceh